Dispersion of deep-sea hydrothermal vent effluents and larvae by submesoscale and tidal currents. (March 2018) - Vic, Clément; Gula, Jonathan; Roullet, Guillaume; Pradillon, Florence
Abstract: Deep-sea hydrothermal vents provide sources of geochemical materials that impact the global ocean heat and chemical budgets, and support complex biological communities. Vent effluents and larvae are dispersed and transported long distances by deep ocean currents, but these currents are largely undersampled and little is known about their variability. Submesoscale (0.1–10 km) currents are known to play an important role for the dispersion of biogeochemical materials in the ocean surface layer, but their impact for the dispersion in the deep ocean is unknown. Here, we use a series of nested regional oceanic numerical simulations with increasing resolution (from δ x = 6 km to δ x = 0.75 km ) to investigate the structure and variability of highly-resolved deep currents over the Mid-Atlantic Ridge (MAR) and their role on the dispersion of the Lucky Strike hydrothermal vent effluents and larvae. We shed light on a submesoscale regime of oceanic turbulence over the MAR at 1500 m depth, contrasting with open-ocean – i.e., far from topographic features – regimes of turbulence, dominated by mesoscales. Impacts of submesoscale and tidal currents on larval dispersion and connectivity among vent populations are investigated by releasing neutrally buoyant Lagrangian particles at the Lucky Strike hydrothermal vent. Although the absolute dispersion is overall not sensitive to the model resolution, submesoscale currents are found to significantly increase both the horizontal and vertical relative dispersion of particles at O (1–10) km and O (1–10) days, resulting in an increased mixing of the cloud of particles. A fraction of particles are trapped in submesoscale coherent vortices, which enable transport over long time and distances. Tidal currents and internal tides do not significantly impact the horizontal relative dispersion. However, they roughly double the vertical dispersion. Specifically, particles undergo strong tidally-induced mixing close to rough topographic features, which allows them to rise up in the water column and to cross topographic obstacles. The mesoscale variability controls at first order the connectivity between hydrothermal sites and we do not have long enough simulations to conclude on the connectivity between the different MAR hydrothermal sites. However, our simulations suggest that the connectivity might be increased by submesoscale and tidal currents, which act to spread the cloud of particles and help them cross topographic barriers. Abstract : Highlights: High-resolution numerical simulations shed light on a submesoscale regime of turbulence at the depth of the Mid-Atlantic Ridge. Submesoscales and tides enhance the relative dispersion of particles and may augment the connectivity between MAR vents. Tidal currents and internal tides double the vertical dispersion of particles and help crossing topographic barriers.